Neutralizing antibodies to SARS-CoV-2 variants of concern: a pediatric surveillance study - Douglas D. Fraser; Devika Singh; Enis Cela; Maitray A. Patel; Maysaa Assaf; Maritza Quintero; Michael Knauer; Michael R. Miller; Melina Bellini; Angela Li; Paul Hahn; Marta Hrek; et al. (Scientific Reports)
Abstract Knowledge regarding the pediatric immune response to SARS-CoV-2 infection and/or vaccination remains limited, particularly for the variants of concern (VOC). Our objective was to evaluate the neutralizing antibody response against SARS-CoV-2 VOC in the naturally infected and/or vaccinated pediatric population. Participants aged 5–12 years who presented to either an outpatient clinic or emergency room were eligible for participation in this study. Participants were divided into four groups based on infection and vaccination status. Plasma was tested using immunoassays targeting anti-SARS-CoV-2 IgG, spike protein, and nucleocapsid. A total of 619 participants met study inclusion. Natural infection was identified in 189/619 children (31%), 284/619 were vaccinated (46%) and 69/619 were both naturally infected and vaccinated (11%). Participants that were vaccinated had received one (n = 169/619; 27%) or two (n = 115/619; 19%) vaccine doses. The median time between the 1st and 2nd vaccine doses was 56 days, interquartile range 50–56. A general upward trend in antibody positivity was observed across all VOC as the study proceeded over a 5-month period. Omicron antibody responses were lower than those of other VOC, both in relation to the percentage of positive cases and over time. Neither asthma nor diabetes altered antibody responses, but antibody titres were reduced for a variety of VOC in those children receiving immunotherapy or with leukopenia. This study demonstrated decreased neutralizing antibody responses against the Omicron variant, regardless of past infection or vaccination status. These findings emphasize the need for continued neutralizing antibody surveillance.